INVESTASI PENGUATAN EKONOMI KREATIF BERBASIS PENDAMPINGAN PRODUKSI USAHA MIKRO HALAL DI DESA SOGIYAN - Iqbal Rafiqi (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
Assistance in the production of halal micro business of sale mamba bananas in Sogiyan village in supporting investment in the development of this creative economy is based on natural resources, namely bananas are found in Sogiyan village but are not utilized to make it more economical. The purpose of this assistance is to make village assets more economical and help the village's creative economy. The results of the production assistance for the sale mamba banana halal mikra business in Sogiyan village are 1). The village head and PKK women welcomed and carried out the training with enthusiasm so as to create delicious and contemporary products to be accepted by all circles. 2). There are still obstacles to online marketing through social media carried out by PKK women and the need for a Village Owned Enterprise (BUMDES) in order to advance the typical businesses of Sogian village.